The professional background of a referring physician predicts the diagnostic yield of small bowel capsule endoscopy in suspected small bowel bleeding - Compare, Debora; Sgamato, Costantino; Rocco, Alba; Coccoli, Pietro; Donnarumma, Durante; Marchitto, Stefano Andrea; Cinque, Sofia; Palmieri, Pietro; Nardone, Gerardo (Endoscopy International Open, 2024)
Background and study aims The diagnostic yield of small-bowel capsule endoscopy (SBCE) in suspected small bowel bleeding (SSBB) is highly variable. Different reimbursement systems and equipment costs also limit SBCE use in clinical practice. Thus, minimizing non-diagnostic procedures is advisable. This study aimed to assess the SBCE diagnostic yield and identify factors predicting diagnostic findings in a cohort of patients with SSBB. Patients and methods In this retrospective cohort study, we analyzed the medical records of patients who consecutively underwent SBCE for SSBB over 9 years. By logistic regression, we identified covariates predicting diagnostic findings at SBCE. Finally, we performed a post-hoc cost analysis based on previous gastroenterologist or endoscopist consultations versus direct SBCE ordering by other specialists. Results The final analysis included 584 patients. Most SBCEs were ordered by a gastroenterologist or endoscopist (74%). The number of SBCEs without any finding was significantly lower in the gastroenterologist/endoscopist group P<0.001). The SBCE diagnostic yield ordered by a gastroenterologist or endoscopist was significantly higher than that by other specialists (63% vs 52%, odds ratio [OR] 1.57; 95% confidence interval [CI] 1.07–2.26, P=0.019). At multivariate analysis, older age (OR 1.7, 95%CI 1.2–2.4, P=0.005), anemia (OR 4.9, 95%CI 1.9–12, P=0.001), small bowel transit time (OR 1, 95%CI 1–1.02, P=0.039), and referring physician (OR 1.8, 95%CI 1.1–2.7, P=0.003) independently predicted diagnostic findings. Implementing prior gastroenterologist or endoscopist referral vs direct SBCE ordering would reduce medical expenditures by 16%. Conclusions The professional background of referring physicians significantly improves the diagnostic yield of SBCE and contributes to controlling public health costs.
Keywords: Endoscopy Small Bowel; Capsule endoscopy; Small intestinal bleeding